Determination of cobalt in vegetable animal foodstuffs by differential pulse adsorptive voltammetry using α-benzil dioxime - Giroussi, S.; Voulgaropoulos, A.; Ayiannidis, A.K.; Golimowski, J.; Janicki, M. (The Science of the total environment, 1995)
A selective and sensitive voltammetric method for the determination of cobalt in vegetable animal foodstuffs is developed. The method is based on the use of α-benzil dioxime (α-BD) as a chelating agent for differential pulse adsorptive stripping voltammetry (DPASV) and is free from zinc interferences. The influence of pH, time and α-BD concentration on the peak resolution and height are discussed. The method was successfully applied in some typical vegetable animal foodstuffs with R.S.D. < 6%.